2017
DOI: 10.1001/jamadermatol.2016.4518
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and Budget Effect Analysis of a Population-Based Skin Cancer Screening

Abstract: IMPORTANCESeveral epidemiological studies show an alarming global increase in incidence of melanoma and nonmelanoma skin cancer.OBJECTIVES To examine the cost-effectiveness of 2 population-based skin cancer screening methods and to assess their budget effect and the influence on skin cancer epidemiological findings. DESIGN, SETTING, AND PARTICIPANTSA Markov model with a latent period of 20 years and a time horizon of 50 years was used to analyze the cost-effectiveness (societal perspective) and budget effect (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Health insurance companies and governments worldwide promote a shift of minor skin surgery from secondary to primary care in order to reduce health care costs [5][6][7]. Accordingly, the Dutch Collaborating Centre of the WHO promotes a shift of BCC care, even though it is unknown whether the quality of BCC care among GPs is sufficient compared to medical specialists.…”
Section: Introductionmentioning
confidence: 99%
“…Health insurance companies and governments worldwide promote a shift of minor skin surgery from secondary to primary care in order to reduce health care costs [5][6][7]. Accordingly, the Dutch Collaborating Centre of the WHO promotes a shift of BCC care, even though it is unknown whether the quality of BCC care among GPs is sufficient compared to medical specialists.…”
Section: Introductionmentioning
confidence: 99%
“…Eight previous economic evaluations of melanoma early detection programmes have been reported: three Australian,35 three US35 and one Belgian36 and UK 37. All studies used long-term Markov or decision-analytic models as we did, and all showed early detection producing a downshift of melanoma stage and improved survival 35.…”
Section: Discussionmentioning
confidence: 90%
“…All studies used long-term Markov or decision-analytic models as we did, and all showed early detection producing a downshift of melanoma stage and improved survival 35. Several studies included the costs for increased case-finding of KCs and benign tumours but only recent studies recognised the importance of quality of life and used QALYs as a primary outcome 36 38 39. Economic evaluations of primary prevention of skin cancer have varied in intervention type and duration but all have shown favourable economic and health benefits 35…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that providing germline BRCA1/2 testing over 50 years to those patients and their relatives amounted to €13,437,897. 43 [38] used a €35,000/QALY threshold, while D'Andrea et al [39] and Areia et al [40] set a threshold of €37,000/QALY in Italy and Portugal, respectively. However, Neuman et al [41] and Naber et al [42] considered a higher cost-utility threshold (€50,000/QALY).…”
Section: Discussionmentioning
confidence: 99%
“…Our results of the one-way sensitivity analyses were not substantially different from the base case, and most of them were below the €37,000/QALY threshold. Besides, our PSA showed that 52.52% of our simulations fell below the €35,000/QALY threshold, 60.56% were below the €37,000/QALY threshold, and 89.12% were below the €50,000/QALY threshold [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%